Bonhoeffer, theology and religion – what do they teach us a for a south-north dialogue? = BONHOEFFER, TEOLOGIA E RELIGIÃO – O QUE ELES NOS ENSINAM PARA UM DIÁLOGO NORTE-SUL? - Frick, Peter (Ciências da religião história e sociedade, 2009)
As the title of this essay indicates, this study engages four distinct themes, namely, Dietrich Bonhoeffer, theology,religion and dialogue. Our task is not so much to examine each of these themes in detail, but to work out a matrix that allows each of the themes to have a specific and important place in a genuine conversation. Our main objective is thus the question of how Bonhoeffer, theology and religion fit together in a coherent and integrative dialogue among theologians of the south and north and by extension between east and west.